Effect of Eggshell Waste as Reinforcement on Physical and Mechanical Properties of Recycled Aluminium Chip AA7075: A Review - Mohamad, Zaleha; Ahmad Daud, Muhammad Firdaus (Research Progress in Mechanical and Manufacturing Engineering, 2020)
The driving force for the application of aluminium metal matrix composites with waste product as reinforcement likes eggshells over ferrous and nonferrous alloys is due to the economic, performance and environmental benefits. Potential of using eggshells as reinforcement was investigated based on the literature review by studying the previous studies of physical and mechanical properties of the composite body. The previous studies were based on results and discussions of the properties which are hardness, compression, density and porosity properties of aluminium metal matrix composite (AMMC). The hardness has been found to increase with increasing of reinforcement composition. The compression strength results are shown related to hardness results. The density has been found to affect the composite density cause influenced by the mass of reinforcement while porosity increased when the empty space between particles increased. Material selection for reinforcement is very important for influencing the properties of AMMC. A consolidated review is being carried out and conclusions are made.